2020
DOI: 10.1161/hypertensionaha.120.15491
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Nitric Oxide Suppresses Action-Potential-Like Transient Spikes and Vasospasm in Small Resistance Arteries

Abstract: Endothelial dysfunction in small arteries is a ubiquitous, early feature of cardiovascular disease, including hypertension. Dysfunction reflects reduced bioavailability of endothelium-derived nitric oxide (NO) and depressed endothelium-dependent hyperpolarization that enhances vasoreactivity. We measured smooth muscle membrane potential and tension, smooth muscle calcium, and used real-time quantitative polymerase chain reaction in small arteries and isolated tubes of endothelium to investigate how dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 52 publications
0
17
1
Order By: Relevance
“…106 A recent study has demonstrated the advantage of T-type calcium channel blockade in suppressing vasospasm in small coronary arteries through EDH-mediated mechanisms. 107 These results shed light on the pleiotropic effects of benidipine on coronary inflammation and vasomotion abnormalities, although benidipine is available exclusively in several Asian countries (eg, Japan, China, Korea, and the Philippines) for the treatment of hypertension and vasospastic angina. 108…”
Section: Calcium Channel Blockersmentioning
confidence: 93%
“…106 A recent study has demonstrated the advantage of T-type calcium channel blockade in suppressing vasospasm in small coronary arteries through EDH-mediated mechanisms. 107 These results shed light on the pleiotropic effects of benidipine on coronary inflammation and vasomotion abnormalities, although benidipine is available exclusively in several Asian countries (eg, Japan, China, Korea, and the Philippines) for the treatment of hypertension and vasospastic angina. 108…”
Section: Calcium Channel Blockersmentioning
confidence: 93%
“…Isolated arteries were mounted in a Mulvany-Halpern wire myograph chamber (model 610, Danish MyoTechnology, Denmark) as described previously ( Smith et al, 2020 ). Artery viability was determined using the α 1 -adrenergic vasoconstrictor phenylephrine (PE, 3 μM; Sigma-Aldrich, MO, United States) to assess SMC function, followed by the EC-dependent agonist acetylcholine (ACh, 10–100 nM; Merck, NJ, United States) to assess EC function.…”
Section: Methodsmentioning
confidence: 99%
“…103 Recruiting MEF to activate K Ca 3.1 and K Ca 2.3, and release of NO, is an essential part of the cycle that entrains vasomotion, and block of either NO synthesis or EDH input each raises vasoreactivity and abolishes sinusoidal vasomotion. 82,91,106 Vasomotion can persist in some form after EC removal, and this may be possible because of input from VSM K Ca 1.1 channels, which are voltage-and Ca 2+sensitive. 103 Vasomotion was of particular interest to Tudor Griffith, and in 1994 with David Edwards, he proposed that the ability of rhythmic changes in artery diameter to switch rapidly from sinusoidal, steady-state oscillations into nonrepetitive patterns including periodic, quasiperiodic, and intermittent activity was not random but characteristic of nonlinear systems classified as "chaotic" and amenable to fractal analysis.…”
Section: Cross Cell Chatter Supports Arterial Vasomotionmentioning
confidence: 99%
“…When both NO and EDH are blocked, the depolarizing spikes in membrane potential become more consistent, and associated with low-amplitude, higher frequency oscillations in vasoconstriction, termed vasospasm. Modified from Smith et al, 106 the time base for membrane potential and tension represents simultaneous recordings.…”
Section: Cross Cell Chatter Supports Arterial Vasomotionmentioning
confidence: 99%